Hubungan Sudut Q-Angle terhadap Functional Knee pada Kasus Patellofemoral Pain Syndrome di RS Efarina Pematangsiantar - Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Togatorop, Margaretha (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2024)
Determine the relationship between Q-angle with knee function in patellofemoral pain syndrome (PFPS) aged 16-19 years old. Method: This research is a non-experimental research in the form of a correlation study to analyze the relationship Q-angle is related to functional knee. A total of 25 students (16-19 years old) from SMA Yadika 3, Karang Tengah. The measuring instrument used a goniometer for the degree of the Q-angle and the Knee Injury and Osteoarthritis Outcome Score (KOOS) for the measurement a functional knee. Results: Correlation test with the Spearment Rank Correlation Test showed a not significant score of p=0.454 (p>0.05) with r= -0.157. Average and standard deviation of degree of the Q-angle is 18.40 ± 2.18 and of the functional knee is 59.26 ± 10.81. Conclusion: There is no correlation between Q-angle and functional knee in Patellofemoral Pain Syndrome.